2001
DOI: 10.1002/mus.1137
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of undiagnosed diabetes and impaired glucose tolerance in patients with idiopathic sensory neuropathy

Abstract: The aim of the study was to determine the frequency of undiagnosed abnormal glucose metabolism in patients with idiopathic sensory neuropathy. Patients were separated into two groups depending on presence or absence of painful symptoms, and an oral glucose tolerance test was performed. Of the 48 patients studied, those with painful symptoms had a higher frequency of abnormal glucose metabolism than literature-based controls, whereas patients without painful symptoms showed no difference. Comparison of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
138
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(160 citation statements)
references
References 6 publications
13
138
1
5
Order By: Relevance
“…The present findings provide a mechanistic basis for the clinical observations of improved nerve function in type 1 diabetic patients treated with C-peptide (40,41). Clinically, painful diabetic neuropathy occurs in patients with pre-diabetes (8,9) and early in the course of diabetic neuropathy in type 2 patients (42,43). This has been linked to deficits in neurotrophic factors such as NGF and impaired insulin action with impacts on neuroeffector peptides like substance P and CGRP (36,38,44).…”
Section: Discussionmentioning
confidence: 66%
“…The present findings provide a mechanistic basis for the clinical observations of improved nerve function in type 1 diabetic patients treated with C-peptide (40,41). Clinically, painful diabetic neuropathy occurs in patients with pre-diabetes (8,9) and early in the course of diabetic neuropathy in type 2 patients (42,43). This has been linked to deficits in neurotrophic factors such as NGF and impaired insulin action with impacts on neuroeffector peptides like substance P and CGRP (36,38,44).…”
Section: Discussionmentioning
confidence: 66%
“…It is likely that some of these patients had undiagnosed diabetes, because people who are overweight are more likely to have diabetes, and there is some evidence that undetected diabetes is associated with at least some cases of neuropathy. 41 Another pos-sibility is that neuropathy is caused in part by nerve compression or by trauma associated with weightbearing. On the other hand, neuropathy may lead to inactivity with resultant weight gain.…”
Section: Clues To Etiologiesmentioning
confidence: 99%
“…However, studies that have investigated the contributions of the individual components have revealed mixed results 15, 16, 17, 18, 19, 20, 21. We have recently shown that diabetes, prediabetes, and obesity are the main metabolic components associated with peripheral neuropathy in a United States obese population 22.…”
Section: Introductionmentioning
confidence: 99%